Potentials Folklore to The Development of Ecotourims in Mappi Region, Papua Province - Susilo, Bambang Eko; Avenzora, Ricky; Hermawan, Rachmad (Media Konservasi, 2018)
Generally, all the society’s elements in Mappi Region recognize the existence of folklor which is rich with the value of life philosophy. Data analysis method used was one score one criteria scoring system which was followed by using SWOT analysis as the basic consideration in statingoptimization strategy of the eco-cultural tourism development. The result of the study revealed that various potential of folklore with material andimmaterial heritage had good meanings and reasonable to be fostered in all aspects of tourism development. The high motivation of the society alsoindicated the great enthusiasm of eco-cultural tourism development in mappi region. It was different in terms of preference and participation in whichscore was far from the optimum value. This indicated the local society’s low knowledge of the importance of culture and folklore utilization asecotourism resources. Therefore, the integration of stakeholders to optimize various development of eco-cultural tourism is needed in order to createmultiplier effect. The strategy of eco-cultural tourism development in mappi region which needs to be done is by optimizing perspective of regionaldevelopment, perspective of social culture, perspective of marketing and perspective of activities and ecotourism program.Keywords: ecotourism, mappi folklor, one score one criteria scoring system, Papua